From “Political Solidarity” to “Solidarity Politics.” Theoretical Directions and Practical Possibilities in Research on Transnational Solidarity - Gęsiarz, Michał (Sensus Historiae, 2023)
In this paper I aim to give a critical overview of theories on the phenomenon of transnational solidarity. On the basis of these theories, I attempt to develop a conceptual framework that makes it possible to gain a deeper understanding of the phenomenon of Norwegian-Polish solidarity in the 1980s. In the first part of the article, I provide an overview of the concepts including the difference between the phenomena of transnational solidarity and humanitarianism. Next, I present general directions in research on Norwegian expressions of transnational solidarity. The last part of the article is dedicated to an attempt to ground the notion of “solidarity politics” as a potentially convenient reference for solidarity movements, which is at the same time an attempt to point to the agency of society in international relations.